Presence of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli and Klebsiella pneumoniae Isolated from Avian Species in a Petting Zoological Garden - Juan Casas-Paul; José Luis Bravo-Ramos; María Guadalupe Sánchez-Otero; Sokani Sánchez-Montes; Sashenka Bonilla-Rojas; Luis Arturo Ortíz-Carbajal; Gerardo Gabriel Ballados-González; Jannete Gamboa-Prieto; Alejandra Chong-Guzmán; Angelica Olivares Muñoz (Journal of Zoological and Botanical Gardens, 2025)
Extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae pose a significant public health risk. As zoos grow in popularity, exotic animals come into closer contact with humans, making them potential reservoirs of ESBLs. However, data on ESBL presence in Mexican zoos remains limited. For this reason, this study aimed to isolate and assess the antimicrobial susceptibility of Enterobacteriaceae that colonize avian species in a petting zoo and to identify any ESBL-producing isolates. Cloacal swabs were collected from 34 healthy birds at Miguel Angel de Quevedo Zoo, Veracruz, Mexico. Samples were analyzed microbiologically and molecularly to detect ESBL-encoding genes. A total of seventeen E. coli and one K. pneumoniae strains were isolated from cloacal swabs of bird species, and multidrug resistance (MDR) was found. The most frequently detected genes were blaCTX-M-1 (16/18) and blaTEM-1 (12/18). The detection of multidrug-resistant (MDR) strains carrying blaCTX-M-1, blaTEM-1, and blaSHV genes highlights the potential role of birds as reservoirs and disseminators of antimicrobial resistance (AMR) in urban environments. To the best of our knowledge, this is the first study conducted in Mexico. In conclusion, MDR ESBL-producing bacteria were found in the fecal microbiota of bird species at a petting zoo in Mexico. The limitations of this study emphasize the need for a One Health approach to analyze the genome-wide isolates and epidemiology of antimicrobial-resistant bacteria in captive zoo animals in Mexico. This would support targeted surveillance efforts and help reduce the emergence and spread of resistant bacteria among zoo animals and visitors.